Simulation Modeling of Rounded-Shape Floating LNG Production and Storage Capacities - Koto, Jaswar; Sanusi, Sanusi (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2014)
Liquefied Natural Gas production processes involve many high profile control systems and equipments that costing a vast amount of investment. Any mistakes in the management decision to select the resources and equipments will cause serious problem aftermath and it will be difficult to meet the expected output. Production processes play very important rules in Liquefied Natural Gas Supply Chain and integration with well models (under water process), storage models, transportation model and receiving terminal models. The main focuses of this paper are to simulate production and storage capacities of Rounded-Shape Floating Liquefied Natural Gas by considering the capacity of every single process and utilization of equipments used and storage design. Simulation modeling can be used as controlling and decision making tool with associated factors such as Front-End Engineering Design rate, capacity of every process and storage design capacity.